Neamine Inhibits Growth of Pancreatic Cancer Cells In Vitro and In Vivo - 刘亚萍 吴艳丽 章晓燕 胡国富 吴云霞 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Neamine, a non-toxic derivative of neomycin, has recently been shown to have antitumor activities in various types of cancers. However, its effect on pancreatic cancer is still unknown. The study aimed to investigate its antitumor activity on pancreatic cancer and the underlying mechanisms. MTT assay was used to observe the effect of neamine on angiogenin（ANG）-induced As PC-1 cell proliferation. Tissue microassay and immunofluorescence staining were used to detect the expression of ANG and its nuclear translocation, respectively. Tumor xenografts were established by subcutaneous inoculation of As PC-1 pancreatic cancer cells into the right flanks of nude mice, and neamine was injected subcutaneously. Immunohistochemistry was done to observe the expression of ANG, CD31 and Ki-67 in tumor xenografts. It was found that neamine blocked the nuclear translocation of ANG effectively and inhibited ANG-induced As PC-1 cell proliferation in a dose-dependent manner. Neamine had anti-tumor effects on As PC-1 xenograft models. Consistently, neamine reduced the expression levels of ANG, Ki-67 and CD31 in tumor xenografts. It was concluded that neamine may be a promising agent for treatment of pancreatic cancer.